The prevalence of menstrual cycle disorders in female athletes from different sports disciplines: A rapid review - Gimunová, M.; Paulínyová, A.; Bernaciková, M.; Paludo, A. C. (International Journal of Environmental Research and Public Health, 2022)
The aim of this study was to rapidly review the literature on the prevalence of menstrual disorders in female athletes from different sports modalities. Articles were searched in the Web of Science and PubMed database in May 2022. A total of 1309 records were identified, and 48 studies were included in the final stage. The menstrual disorders described in the included studies were primary (in 33% of included studies) and secondary amenorrhea (in 73% of included studies) and oligomenorrhea (in 69% of included studies). The prevalence of menstrual disorders among the studies ranged from 0 to 61%. When data were pooled according to discipline (mean calculation), the highest prevalence of primary amenorrhea was found in rhythmic gymnastics (25%), soccer (20%) and swimming (19%); for secondary amenorrhea in cycling (56%), triathlon (40%) and rhythmic gymnastics (31%); and oligomenorrhea in boxing (55%), rhythmic gymnastics (44%) and artistic gymnastics (32%). Based on the results of this review, the study supports the literature of the higher prevalence of menstrual disorders in gymnastics and endurance disciplines. However, team sports modalities such as volleyball and soccer also presented a considerable percentage of menstrual disorders compared to the general population. It reinforces the importance of coaches and physicians paying attention to athletes` menstrual cycle as the occurrence of menstrual disorders can be associated with impairment on some health components.